Improving the Participationof Agro-Pastoralists in Climate ChangeAdaptation and Disaster Risk ReductionPolicy Formulation: A Case Studyfrom Keiyo District, Kenya - Kipkorir, Emmanuel Chessum; Mugalavai, Edward Musungu; Kwonyike, Andrew Chepkok; Ng’weno, Caroline; Songok, Charles Kipkorir (My University, 2011)
rowing scientific evidence suggests that climate change will acceler-ate weather extremes and increase human vulnerability to disasters. Exposure ofagro-pastoralists to erratic rainfall and cyclical droughts leads to frequent cropfailures and livestock losses, with additional shocks from economic perturbationsand erosion of household assets depriving this vulnerable group of ‘‘insurance’’against adverse risks, driving them from a state of vulnerability to destitution.Despite the growing global agitation to mainstream community-based strategiesfor climate change adaptation (CCA) and disaster risk reduction (DRR) in Kenya,existing institutional and policy formulation processes rarely incorporate the viewsand experiences of agro-pastoralists. This leads to policies that are neitherresponsive nor accountable to vulnerable groups. This paper identifies existing community strategies for CCA and DRR in Keiyo district and assesses their levelof participation in policymaking, as well as key challenges and opportunities formainstreaming agro-pastoralist involvement in policy formulation. The data wasobtained through participatory approaches involving focus group discussions(FGDs), questionnaires and structured interviews. It is evident from the findings ofthe study that while agro-pastoralists have developed localised strategies forCCA and DRR, these are not fully recognised by existing government policyprocesses. Therefore, efforts should be made to mainstream the participation ofagro-pastoralists in CCA and DRR policy formulation processes.
Keywords: Agro-pastoralists; Livelihoods; Climate change adaptation; Disaster risk reduction; Policy formulation